1998
DOI: 10.1016/s0167-5699(97)01204-8
|View full text |Cite
|
Sign up to set email alerts
|

Give us this day our daily germs

Abstract: Modern vaccinations, fear of germs and obsession with hygiene are depriving the immune system of the information input upon which it is dependent. This fails to maintain the correct cytokine balance and fine-tune T-cell regulation, and may lead to increased incidences of allergies and autoimmune diseases. If humans continue to deprive their immune systems of the input to which evolution has adapted it, it may be necessary to devise ways of replacing it artificially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(195 citation statements)
references
References 10 publications
10
182
0
3
Order By: Relevance
“…Th2 responses are thought to be protective against parasite-mediated disease (60) but are associated with allergic disorders (59,61). It has been suggested that induction of Th2 cells or failure to mount a Th1 or regulatory T-cell response to foreign antigens in childhood may enhance atopic disease (10,49). It is therefore conceivable that changing patterns of microbial exposure through infection and vaccination in childhood may contribute to the observed increase in atopic disease and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 responses are thought to be protective against parasite-mediated disease (60) but are associated with allergic disorders (59,61). It has been suggested that induction of Th2 cells or failure to mount a Th1 or regulatory T-cell response to foreign antigens in childhood may enhance atopic disease (10,49). It is therefore conceivable that changing patterns of microbial exposure through infection and vaccination in childhood may contribute to the observed increase in atopic disease and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that germ-free animals, which are exposed to dietary antigens but not bacterial antigens, possess only a rudimentary immune system. The significance of the microbial flora in relation to host immunity is further highlighted by the fact that the decreased exposure to microbes in Western society has been correlated with an increased incidence of atopic and autoimmune diseases in adults (Rook & Stanford, 1998). The mechanisms by which microbes influence the phenotype and function of lymphoid cells associated with the GALT are largely unknown, but are likely to involve complex events that are probably triggered following the 'normal' route of antigen uptake and processing.…”
Section: Antigen Exposure and Immune Developmentmentioning
confidence: 99%
“…Th1 and Th2 responses and their balance appear to be critical in mounting the strong cytotoxic responses required for pathogen clearance. The Th1-Th2 balance is, in turn, thought to be influenced by microbial exposure (Rook & Stanford, 1998), and perhaps suggests that there is an optimum flora in early life that can promote a healthy intestine and optimize its immune function.…”
Section: Antigen Exposure and Immune Developmentmentioning
confidence: 99%
“…Its objective is the inhibition of IgE sensitization (67). In fact, several studies have suggested that the process of sensitization to foods and (255,256) Upholstered furniture and wall-to-wall carpets (86) Early use of vaccination (257) Central heating systems and/or humidi®ers (10) Early use of antibiotics (258,259) New building materials (244, 267) Changes in intestinal¯ora (260) Early exposure to indoor/outdoor air pollution (261) More time spent indoors (89) Intrauterine immunity (261) Increase in furred pets indoors (88) Dietary factors (262) Breast-feeding (263) Socioeconomic factors (264) inhalant allergens might be initiated in the last months of pregnancy (14, 68±70). Theoretically, this should be the best way to reduce the prevalence of allergic diseases in the future.…”
Section: Prevention Strategiesmentioning
confidence: 99%